Autoria e movimentos de sentido nas gramáticas brasileiras contemporâneas do português - Agnaldo Almeida de Jesus (2019)
It is the objective of this work to understand the gestures of interpretation (of authorship) of contemporary Brazilian grammarians and the effects of meanings produced by them. Such subjects construct (themselves) and formulate meanings about the language, grammar andTHE teaching of both, etc. in a certain socio-historical context, that is, the end of the 20th century and the beginning of the 21st century in Brazil. They are, thus, inserted in a memory/ tradition of knowing about the language, built as specificity of ours from the nineteenth century, above all. In order to reach this objective, we take as an object of analysis theintroductory texts (summary, preface, presentations, introductory chapters, etc.) of five contemporary Brazilian grammars of the Portuguese language by different authors. These are: the Modern Portuguese Grammar (Moderna Gramática Portuguesa), by Evanildo Bechara(2015); the Grammar of Uses of Portuguese (Gramática de Usos do Português), by Maria Helena de Moura Neves (2011); the New Grammar of Brazilian Portuguese (Nova Gramática do Português Brasileiro), by Ataliba Teixeira de Castilho (2014); the Grammar of BrazilianPortuguese (Gramática do Português Brasileiro), by Mario Alberto Perini (2010); and the Standard Portuguese Grammar (Gramática da Língua Portuguesa Padrão), by Amini Boainain Hauy (2015). From the theoretical-methodological point of view, we rely on Discourse Analysis, notably in the works of Michel Pêcheux and Eni Orlandi, articulated tothe studies of the History of linguistic ideas, developed since the end of the 1980s in Brazil. The analysis of the discursivities materialized in the mentioned linguistic instruments points to the production of different effects of meanings, be they systematization, revision and updating of grammatical (traditional) theory, be they distancing from the normative/prescriptive description model of school grammars, also known as "traditional". The formulation of these effects is constitutively related to the fact that the authors, when inserting themselves with their interpretative gesture in the space of the contemporary grammar, find at least two great discursive formations (DF) - the DF of Modern Linguistics and the DF ofTraditional Grammar, which cut the text in relation to dominance, and occupy different subject-positions, such as (traditional-)grammarian and (grammatic-)linguist. Therefore, it is in the contact-confrontation of discourses produced from the place of grammatical Tradition and modern Linguistics, with their nomenclatures, theoretical models and analysis etc., of the place of the State, with the set of institutional injunctions and determinations, such as the NGB, laws, teaching programs, etc., and the proper order of discourse, always subjectto misconception in history, that grammarians construct (themselves) and formulate sayings and knowledge about the Portuguese language in contemporary times.